STRUCTURAL DESIGN OF MIXED-USE BUILDING IN DELI SERDANG - Louis Gunawan, Brandon
Mixed Use Building Deli Serdang functions as a shopping center, office, and apartment. Mixed use building is made to maximize the function of the building while minimizing the space requirement and mobility of its occupants. This building consists of basements, podiums, office tower, and apartment tower. Structural design of Mixed-Use Building in Deli Serdang consists of reinforced concrete structural elements, such as RC beam, RC column, RC slab, and RC shear wall. These structural elements are designed according to SNI 2847:2019. The design loads for this building are determined according to SNI 1727:2020 and ASCE 7- 16. Mixed-Use Building in Deli Serdang will also be designed for earthquake resistance according to SNI 1726:2019. The earthquake resistance parameters checked for Mixed-Use Building in Deli Serdang consists of structure fundamental period, equivalent lateral force, inter story drifts, P-Delta effect, dual system requirement, horizontal irregularity, vertical irregularity, and redundancy factor. These parameters are checked according to SNI 1726:2019. The reinforcement for structural elements is designed according to the principle of design for capacity using the LRFD method. Structural loads will be amplified by an amplification factor, whilst the structural element’s capacity will be reduced by a reduction factor according to the designed capacity (axial, flexure, shear, torsion). The structural system chosen for the building is a dual system, combining the Special Moment Resisting Frame (SMRF) and the Special Structural Wall (SSW). Structural modeling and analysis are done using CSI ETABS to execute the one step, linear dynamic response spectrum analysis. All reinforcement design for RC beams and transversal reinforcement for columns are designed manually, longitudinal reinforcement for slabs are designed using CSI SAFE, and the longitudinal reinforcement for columns and shear walls are designed using spColumn.